A Study Of Service Quality For Passengers Of The Airline Industry - Kouhpaie, Mahnoush (2008)
The primary objective of this study is to develop a reachable, affordable and reliable service strategy (SERQUAL) to upgrade the existing SERQUAL for enhancement of loyalty among the passengers.